Expanding access to biotherapeutics in low-income and middle-income countries through public health non-exclusive voluntary intellectual property licensing: considerations, requirements, and opportunities. Issue 1 (January 2023) - Morin, Sébastien; Segafredo, Giulia; Piccolis, Manuele; Das, Aditi; Das, Meghmala; Loffredi, Nicola; Larbi, Amina; Mwamelo, Kim; Villanueva, Elena; Nobre, Sandra; Burrone, Esteban
Summary: Biotherapeutics, such as recombinant proteins and monoclonal antibodies, have become mainstays of modern medicine as shown by their increasing number in the WHO Model List of Essential Medicines. However, despite frequently offering clinical advantages over standards of care, they remain largely out of reach for populations in low-income and middle-income countries (LMICs), partly because of high costs. Accordingly, the WHO Model List of Essential Medicines Expert Committee has requested that the Medicines Patent Pool explore intellectual property licensing to address this challenge. We therefore investigated how licensing could successfully improve affordability of and timely access to biotherapeutics in LMICs, by leveraging expert consultations, literature analysis, and internal technical knowledge. The key elements identified as relevant to support access to affordable biosimilars in LMICs through licensing include: prioritising potential biotherapeutic targets according to their potential for public health impact; supporting biosimilar product and clinical development (including through technology transfer to expedite regulatory approval); and facilitating biosimilars' entry and use in LMICs (by meeting procurement, supply chain, and health system requirements).